5(4-3x)-2(10-4x)=5x

Simple and best practice solution for 5(4-3x)-2(10-4x)=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4-3x)-2(10-4x)=5x equation:



5(4-3x)-2(10-4x)=5x
We move all terms to the left:
5(4-3x)-2(10-4x)-(5x)=0
We add all the numbers together, and all the variables
5(-3x+4)-2(-4x+10)-5x=0
We add all the numbers together, and all the variables
-5x+5(-3x+4)-2(-4x+10)=0
We multiply parentheses
-5x-15x+8x+20-20=0
We add all the numbers together, and all the variables
-12x=0
x=0/-12
x=0

See similar equations:

| 0=10n^2+11n-21 | | (2/7)=(6x/4x+17) | | 5/7x+1/4=3/7-2/7x+3/7 | | 18x=9000 | | 3p2-30p+48=0 | | 3.6z+1.3=0.2(z-3) | | 4.2x-2.7-5.9x=0.7x-2.7 | | -8y^2=18y-5 | | -250)x5=1355 | | 6x3-16x2-32x=0 | | 2x/2+4x/2=2 | | M/20=m | | 3/4r-4=20 | | x2/5-7x1/5-8=0 | | 2/3b+5=15-b | | x2/5-7x1/5-8=8 | | 162+16m=450 | | 34n-162=450 | | 2×(x+3)=x+18 | | 3x+203=300 | | 10=-0,5x+2 | | x^2+10x-350=0 | | y/4-15=45 | | x(x+3(6-3x)+2x)=6(2X3-1) | | x(x+3(6-3x)+2x)=6(2X-1) | | t^2+100t+6=0 | | x2-24=300 | | 9x+6=9(x+8)= | | x+(4-x)=5(x+1)+x | | 360/20=x/12 | | 6z=4z-3 | | 7z+8=6 |

Equations solver categories